2022
DOI: 10.7759/cureus.27972
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Prevalence of Uncorrected Refractive Error and Other Ocular Morbid Conditions in School Children of Industrial Area in a Non-metro City in India

Abstract: Purpose This study aims to estimate the prevalence of uncorrected refractive error and ocular morbid conditions in school-going children of the Pimpri Chinchwad Municipal Corporation (PCMC) industrial belt. Methods Ocular examination was done in a well-equipped mobile clinic on school premises in the presence of a school teacher using visual acuity (VA) charts, autorefractometer, retinoscope, and handheld slit lamp. For the age group of 5-6 years, Lea symbols and HOTV charts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
3
1
1
Order By: Relevance
“…8 The prevalence of hyperopia (3.36%) and astigmatism (5.75%) was similar to a study conducted in a city in India. 7 Similarly, it is higher than the previous study done in Pokhara, 9 and in a multistate study in India which might be due to the smaller population size in this study. 10 The prevalence of refractive error in this study is 18.5%, which is higher than the study done in Palpa (9%).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…8 The prevalence of hyperopia (3.36%) and astigmatism (5.75%) was similar to a study conducted in a city in India. 7 Similarly, it is higher than the previous study done in Pokhara, 9 and in a multistate study in India which might be due to the smaller population size in this study. 10 The prevalence of refractive error in this study is 18.5%, which is higher than the study done in Palpa (9%).…”
Section: Discussioncontrasting
confidence: 61%
“… 5 , 6 In a previous study of 3054 children, Myopia was seen in 204 (6.68%) children, hypermetropia in 16 (0.52%) children, and astigmatism in 148 (4.85%) children which is almost similar to our study in which Myopia was seen in 9.4% children followed by astigmatism 5.75%, and hyperopia 3.4%. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakare et al examined 3,054 school-going children aged 11-15 years of Pimpri Chinchwad Municipal Corporation in India and found 368 (12.04%) children with uncorrected REs. Myopia was found in 204 (6.8%) participants, followed by astigmatism in 148 (4.8%) and hypermetropia in 16 (0.53%) subjects [ 22 ]. Basu et al also reported 457 (15.22%) prevalences of RE out of 3,002 participants; myopia was found in 418 (91.47%), followed by hypermetropia in 21 (4.6%) and astigmatism in 18 (0.04%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 Berdasarkan penelitian di India oleh Bakare dkk., miopia ditemukan sebanyak 6,68% pada anak dengan klasifikasi Simple Myopic Astigmatism (SMA) sejumlah 2,39% dan Compound Myopic Astigmatism (CMA) sejumlah 1,24%. 32 Dalam penelitian astigmatisma oleh Ijaz dkk. yang dilakukan di Pakistan, didapatkan simple myopic astigmatism 13,8%, compound myopic astigmatism 32,3% dan mixed astigmatism 8,4% yang selanjutnya apabila tidak ditangani tepat waktu maka dapat menyebabkan ambliopia, sehingga skrining yang tepat dapat mencegah anak dari kehilangan penglihatan permanen karena ambliopia.…”
Section: Pembahasanunclassified